KEPASTIAN HUKUM UPAYA HUKUM PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 23/PUU-XIX/2021 (ANALISA PUTUSAN MAHKAMAH AGUNG NOMOR: 647 K/PDT- SUS-PAILIT/2021). - Rif'at, (2024)
The Judge's decision should also provide balanced justice for Insurance Customers who ask for their rights against the Insurance Company, considering that the Insurance Customer has asked the OJK to submit a PKPU and Bankruptcy application against the Insurance Company but did not get an answer from the OJK, resulting in a legal vacuum regarding further efforts that can be made by the Customer in obtaining their rights from the Insurance Company. This study aims to determine the legal certainty of the Supreme Court cassation decision Number: 647 K/Pdt- Sus-Bankruptcy/2021 after the Constitutional Court decision Number 23/PUU-XIX/2021, this research is a normative juridical research, the results of this study indicate that there are several possibilities that occur, legal certainty after the Constitutional Court decision Number 23/PUU-XIX/2021 against Supreme Court decision Number: 647 K/Pdt- Sus-Bankruptcy/2021 which opens up space for an exclusive cassation appeal to the debtor against bankruptcy originating from PKPU due to the rejection of a peace proposal to overcome the legal loophole for deviations made by creditors who have moral hazard to bankrupt the debtor, is not legally reasonable. The contradiction between these two decisions (legal antinomy) above, according to legal experts, will be returned to legal principles, in this case the principle of lex posteriori derogat legi priori (the new law overrides the old law) which is used as a solution to resolve the contradiction of the above legal rules.